Upaya Meningkatkan Hasil Belajar Siswa Mata Pelajaran Akidah Akhlak dengan Menggunakan Model Pembelajaran Berbasis Naturalistik Eksistensial Spiritual - wahyudi, Dedi; Agustin, Nelly (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2018)
The purpose of this study was to find out based on the existential spiritual naturalistic learning model and student learning outcomes. This research is included in the type of research design literature. References obtained in the form of books, journals, articles, and other scientific works. The writing style used in this study is descriptive. This writing is done with an analytical approach and comparison between library sources that have been obtained. Using this naturalistic existential-based expression model can improve student learning outcomes. Both learning outcomes from aspects of cognitive (knowledge), affective aspects (morals) and psychomotrik aspects (skills / skills). The intelligence of students has the potential to improve learning outcomes. No exception on the subject Akidah Akhlak, which is in need of understanding and implementation of the contents of teaching materials. Such intelligence is naturalistic existential and spiritual. It is concluded that these three intelligences are dominantly average owned by the students. When associated with subjects of moral aqid and learning model, existential natural and spiritualistic intelligence is very relevant to teaching materials and learning frames. It appears that student learning outcomes are increasing with the use of this existential spiritualistic-based naturalistic learning model. Increased learning results seen from good morals and good students in accordance with existing norms. Also seen from the results of understanding through the evaluation of side.